Composition of gastropods in mangroves of Tanjung Dawai and Pulau Sayak, Kedah - Faezah, P.; Farah, H.S. (Penerbit Universiti Kebangsaan Malaysia, 2011)
A total of 426 individuals from six families, six genera and ten species were collected from Tanjung Dawai while a total of 351 individuals from five families, five genera and six species were collected from Pulau Sayak. Six families that were found from Tanjung Dawai were Littorinidae, Neritidae, Potamididae, Ellobiidae, Muricidae and Assimineidae while five families that were found from Pulau Sayak were Littorinidae, Ellobiidae, Muricidae, Assimineidae and Naticidae. The abundant species at both mangrove areas were Cerithidea cingulata and Naticidae sp. Shannon Diversity Index and Evenness Index for Tanjung Dawai were 1.95 and 0.85, respectively. Shannon Diversity Index and Evenness Index for Pulau Sayak were 1.27 and 0.71, respectively. Both of the mangroves habitats of Tanjung Dawai and Pulau Sayak, Kedah appeared to have low snail species diversity but still sustain some common gastropod families of tropical mangroves. It is essential to have an economically and ecologically sound management plan in order to make the mangroves ecologically viable as well as a source of economy.